A decision-making framework for life-cycle energy and seismic loss assessment of buildings. Issue 7 (3rd July 2023) - Mohammadgholibeyki, Negar; Nazari, Farnaz; Venkatraj, Varusha; Koliou, Maria; Yan, Wei; Dixit, Manish; Sideris, Petros
Abstract: The integration of building seismic losses and environmental impacts is a key step toward the improvement of building design approaches accounting for resilience and sustainability in parallel. A decision-making framework including the life-cycle energy assessment and seismic loss estimation is proposed in this study in order to investigate the trade-offs between buildings' environmental sustainability and reducing seismic loss. The framework includes a Pareto front analysis to reach a balance among the criteria. Building operational energy, embodied energy, seismic repair cost, and injuries were the performance metrics considered. The framework was applied to three reinforced concrete building designs including low- to high-rise buildings along with six exterior wall assemblies and four Window-to-Wall-Ratios. The contradictory trend among the performance metrics underlines the importance of merging these concepts for the development of the current building design methodologies. The hypervolume indicator was computed for each building's Pareto front set to evaluate the quality of Pareto front design solutions. The results showed that compared to the 20-story building, the 2- and 12-story buildings have higher number of Pareto solution points and the solutions are of higher qualities in terms of diversity and proximity to the true Pareto front based on the hypervolume indicator solutions.